Effect of Different Cooking Methods on Lipid Content and Fatty Acid Profile of Red Mullet ( Mullus barbatus ) - Francesca Biandolino; Ermelinda Prato; Asia Grattagliano; Isabella Parlapiano (Polish Journal of Food and Nutrition Sciences)
This study investigated the effect of five in-house cooking methods (grilling, oven-cooking, frying, microwaving, and boiling) on lipid content and fatty acid composition in red mullet ( Mullus barbatus ). Moreover, the nutritional quality of the lipid fraction was evaluated by determining a number of lipid nutritional quality indices (LNQI). Moisture content of red mullet decreased after cooking, with the exception of boiled fish, while the lipid content significantly increased after microwave treatment and frying. After the latter, a ten-fold increase in lipid content was noted compared to fresh fish (from 2.1 to 21.1 g/100 g wet matter). All cooking methods caused significant changes in the fatty acid (FA) profile of M. barbatus . The content of saturated fatty acids (SFA) varied significantly between raw and cooked fish with the lowest values determined for fried sample. Monounsaturated fatty acid (MUFA) content increased after oven cooking and frying, while polyunsaturated fatty acid (PUFA) content showed an opposite trend. The eicosapentaenoic acid (EPA) and docosahexaenoic (DHA) were the dominant fatty acids among n 3 acids in all samples. EPA+DHA contribution in total FAs was significantly lower in the samples after oven cooking (19.6% total FAs) and frying (4.99% total FAs) than in the raw (25.5% of total FAs) fish. The n 3/ n 6 ratio (range 1.25–3.65) decreased significantly after cooking; however, it remained above the recommended values for a healthy human nutrition (1:5). The PUFA/SFA ratio was between 0.69 in fried and 1.02 in boiled fish, both being greater than those recommended by the WHO/FAO [2003]. Atherogenicity index value decreased significantly after the cooking particularly in fried fish. The polyene index (PI), as a measure of PUFA damage, was in the range of 0.42–1.18. Although all cooking methods affected the FA profile, based on LNQI, it can be concluded that barbecue-grilling and boiling were the best cooking methods for healthy eating, due to their lowest effect on essential FAs.